2005
DOI: 10.7589/0090-3558-41.3.611
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the Ross River Virus in Captive Marsupials in Urban Areas of Eastern New South Wales, Australia

Abstract: Serum samples collected from 224 tammar wallabies (Macropus eugenii) in two captive populations in urban areas in eastern New South Wales Australia, between December 1999 and May 2004, were tested for antibodies to Ross River virus (RRV). In one population in northwest Sydney, 21 animals (11%) tested positive, and in another population in Newcastle, New South Wales, thirteen (33%) of the animals were positive. Antibodies were detected in four of 11 wallaroos (Macropus robustus) (36%) but not in parma wallabies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…A serosurvey of captive marsupials undertaken in urban New South Wales demonstrated that tammar wallabies (M. eugenuii) were commonly infected by RRV (Old and Deane 2005). These data support the possibility of marsupials serving as amplifying hosts for RRV in urban areas in Australia.…”
Section: Potter Et Almentioning
confidence: 73%
“…A serosurvey of captive marsupials undertaken in urban New South Wales demonstrated that tammar wallabies (M. eugenuii) were commonly infected by RRV (Old and Deane 2005). These data support the possibility of marsupials serving as amplifying hosts for RRV in urban areas in Australia.…”
Section: Potter Et Almentioning
confidence: 73%
“…Like all alphaviruses, the virus is maintained in transmission cycles between its mosquito vector and vertebrate hosts. In the case of RRV the predominant vectors are the mosquitoes Culex annulirostris and Aedes vigilax and the vertebrate hosts are commonly found to be native marsupials (Harley et al, 2001;Old & Deane, 2005;Oliveira et al, 2006). In Australia, there are between 5,000 to 8,000 cases of RRV reported annually (Harley et al, 2001), with patients displaying symptoms of arthritis, arthralgia, myalgia, fatigue, febrile illness and rash (Fraser, 1986;Harley et al, 2002;Harley et al, 2001).…”
Section: Ross River Virus (Rrv)mentioning
confidence: 99%
“…RRV is a positive-sense RNA virus that circulates endemically in Australia and the South Pacific (4) and is maintained in transmission cycles between its mosquito vector and vertebrate hosts (13). In Australia, roughly 5,000 cases of RRV are reported annually (4), with symptoms of arthritis, arthralgia, myalgia, fatigue, febrile illness, and rash (4,14,15).…”
mentioning
confidence: 99%